Wilson's disease: A rare autosomal recessive disorder of copper metabolism - Pradhan, RR; Gupta, J (Journal of Chitwan Medical College, 2014)
Wilson’s disease is an autosomal recessive disorder caused by mutations in the ATP7B gene, a membrane-bound copper-transporting ATPase. Clinical manifestations are caused by copper toxicity and primarily involve the liver, the brain and the eye. Because effective treatment is available, it is important to make this diagnosis early. We report a patient who developed features of neurological and ocular manifestations: incoordination and tremor and blurring of vision with presence of Kayser-Fleischer ring circling the cornea but no signs of hepatic dysfunction. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10866 Journal of Chitwan Medical College 2014; 4(2): 51-54